THE EFFECTIVENESS OF USING KEELER'S STRATEGY IN SINGLING OUT EDUCATION ON THE LEVEL OF PERFORMANCE OF SOME BASIC SKILLS IN BELLY CRAWL SWIMMING FOR BEGINNERS - Dr. Ihab Saadi Mohammed ALSHGLAWI (Scholar Express Journal, 2022)
This research aims to identify the effectiveness of the use of Keeler's strategy in singling out education at the level of performance of some basic skills in swimming crawling on the abdomen for beginners, the researcher used the experimental approach due to its appropriateness to the nature of the current research. Post-pre-measurement for both groups, how much the research community included all children of the age group of (8-11) years (males) in swimming education classes at the Wafer Academy for swimming education during the summer semester 2019/2020, and the most important conclusions exceeded the experimental group that used the educational program Prepared with Keeler's strategy to individualize learning on the control group that used the traditional method (verbal explanation and practical model), which indicates the effectiveness of the educational program and its impact on learning to crawl on the belly for beginners children. Researching and having a positive impact on the level of physical and skill performance of children.
Keywords: Keeler's strategy; performance; belly crawl swimming.